Key concepts in development geography - Potter, Robert B. (Los Angeles, [Calif.] ; London : SAGE, 2012)
Organized around 20 short essays, this introductory text provides students with the core concepts that form contemporary research and ideas within the development geography discipline. It includes over 20 key concept entries that provide comprehensive definitions, explanations and evolutions of the subject.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Human geography; Economic development; Economic geography